The Influence of Infrastructure Development on Economic Growth in the Province Papua Year 2006 – 2020 - Ince Weya; Nancy Nopeline; Darwin Damanik (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to analyze the effect of infrastructure development on economic growth in Papua Province. This study uses secondary data taken from the Central Statistics Agency (BPS) of Papua Province for the period 2006 - 2019. The analytical tools are descriptive and regression using time series data. The results showed that the dependent variable such as the number of educational facilities and health facilities had a positive effect on economic growth in Papua Province. Given the results, the local government should pay more attention to allocating development expendictures for energy, the availability of special electricity infrastructure, the number of Puskesmas and schools to have a significant and positive influence on economic growth in Papua Province.